2019
DOI: 10.1152/ajpcell.00102.2019
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis engagement and bladder urothelial cell-derived exosomes recruit mast cells and induce barrier dysfunction of bladder urothelium after uropathogenic E. coli infection

Abstract: The specific regulatory mechanism of bladder urothelial barrier dysfunction after infection with uropathogenic Escherichia coli (UPEC) is still unclear. The cross talk between bladder urothelial cells and mast cells may play an important role during UPEC infection. In this study, the pyroptosis of urothelial cells was investigated after UPEC infection both in vivo and in vitro. The levels of IL-1β and IL-18 in exosomes derived from bladder urothelial cells after UPEC infection were detected. The role of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…10,33 Our laboratory has recently shown a key role of NLRP3 inflammasomes in infectious cystitis. 34 Inflamed muscles are weakened and can fatigue easily. 35 In bladder outlet obstruction, the activation of NLRP3 induces inflammation and bladder hypertrophy and inhibits the activation of NLRP3 decrease in void volume characteristics of irritative voiding symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,33 Our laboratory has recently shown a key role of NLRP3 inflammasomes in infectious cystitis. 34 Inflamed muscles are weakened and can fatigue easily. 35 In bladder outlet obstruction, the activation of NLRP3 induces inflammation and bladder hypertrophy and inhibits the activation of NLRP3 decrease in void volume characteristics of irritative voiding symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The NLRP3 inflammasome is closely related to bladder inflammation which mediates the biochemical, histological, and physiological inflammation in cyclophosphamide‐induced hemorrhagic cystitis 10,33 . Our laboratory has recently shown a key role of NLRP3 inflammasomes in infectious cystitis 34 . Inflamed muscles are weakened and can fatigue easily 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, even though limited studies have been published, other bacterial infections have been shown to induce EV release that can impact the host. For example, during uropathogenic E. coli infection urothelial cells released exosomes were capable of recruiting mast cells and inducing bladder urothelium barrier dysfunction in a pyroptosis dependent manner [ 78 ]. Exosomes derived from serum of patients with chronic gastritis and positive for Helicobacter pylori stimulated soluble IL-6 receptor (R) in human gastric epithelial cells (GES-1), further resulted in the release of pro-inflammatory cytokine IL1-α.…”
Section: Evs Released During Bacterial Infection Impact Biological Functionmentioning
confidence: 99%
“…Moreover, infection by Uropathogenic E. coli (UPEC) was shown to induce pyroptosis in bladder urothelial cells and release of IL-1β and IL-18 in the form of exosomes. As a consequence, mast cells migrate in the site of infection and worsen the damage to the barrier function of bladder urothelium (160).…”
Section: Induction Of Pyroptosis and Other Types Of Cell Death By Bacmentioning
confidence: 99%
“…These findings were further supported by the detection of heightened levels of sera and urine IL-18 in SLE patients, especially those with active lupus nephritis (177, 178). As mentioned above, bacterial infections are well-known triggers of pyroptosis (33), and common pathogens in SLE patients including E. coli and Salmonella are models of pyroptosis (155, 156, 158, 160, 179), and therefore the increased levels of this category of cell death may be due to subclinical infections causing tissue damage without generalized signs of disease manifestation. Together, these findings strongly suggest that infectious pyroptosis may play a pathogenic role in releasing host nuclear autoAgs in SLE.…”
Section: Induction Of Pyroptosis and Other Types Of Cell Death By Bacmentioning
confidence: 99%